Use of Failure Mode and Effects Analysis in Improving Safety: A case Study in An Oil Company - Malihe Kolahdouzi; Gholam Hossein Halvani; Ebrahim Nazaripour Abdehgah; Maryam Rostami Aghdam shendi; Mohsen Yazdani aval (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: The Failure Mode and Effects Analysis (FMEA), first of all, identifies dangerous modes in a process and, then, provides proper control measures that are required to reduce the level of risk. This study aims to investigate the risk level before and after the implementation of control measures in an edible oil factory. Methods: This cross-sectional study was conducted in an edible oil factory in Tehran, Iran. The FMEA technique was used to identify failure modes related to equipment that existed in five units of this factory. After that, in all units, Risk Priority Numbers of all the processes were assessed on the basis of the FMEA method. With regard to the Risk Priority Number (RPN), some control measures were taken to reduce the risk of events. After nine months, risk assessment was repeated, and primary and secondary RPNs were compared with each other to investigate the effects of interventions. Results: The results showed that the highest probability of danger was related to the installation unit. The probability of danger in this unit before and after interventional actions was 4.5 and 3.25 respectively and the highest degree of severity was related to tool production. The marginal homogeneity test showed the positive effect of control measures on the risk level in the factory. There was a significant inference between before- and after-data in RPN in the unit tool production, neutralization unit, and installation unit. The Tests of Repeated Measure showed that there was a statistically significant inference between before- and after-data in the total average of RPN criterion (pvalue < 0.001). Conclusion: It can be concluded that the high risk level in the factory units was reduced after the application of interventional corrective measures. These actions have been useful. It can be mentioned that the FMEA has been successfully able to identify and control the level of risk in this factory.